Behavior assessment of asymmetrical building with concrete damage plasticity (CDP) under seismic load - Patrick de Oliveira Batista da Costa; Rbia Mara Bosse; Gustavo de Miranda Saleme Gidro (Fracture and Structural Integrity)
According to the research conducted, the asymmetric multi-storey buildings are complex and suffer from severe damage caused by increased torsional response. This paper addresses the behavior assessment of setback building with irregularity in the plan under severe seismic events such as Kobe earthquake. Using a three-dimensional model, the structure is subjected to seismic records in the three directions through ground accelerations. Nonlinear time-history analyses are employed to evaluate the dynamic response of the building. The mechanical model describes physical nonlinear behavior with evolution of damage and plasticity showing the regions of cracking propagation, mainly the columns-beams connections, corroborating the weak column and strong beam concept. The slabs did not present significant danification with damaged regions lumped on the borders of the first floors